ANALYSIS OF THE ROLE OF SOCIAL CAPITAL IN THE SUSTAINABILITY OF MSMES AT THE KALIMADU CULINARY CENTER, GORONTALO CITY - Harold, Rudi; Pakaya, Lidyawati; Uwewengo, Yalla; Tahir, Mutawaqil; Yarkuran, Mira; Bidjuni, Moh. Nabil Putra (Academic Solution Publisher, 2025)
This study aims to analyze the role of social capital in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the Kalimadu Culinary Center, Gorontalo City. The approach used was descriptive qualitative with five MSMEs as key informants, selected purposively based on age, type of business, and length of operation. Data collection techniques included in-depth interviews, participant observation, and documentation, while data analysis was conducted through thematic analysis to identify relevant patterns, themes, and categories. The results showed that social capital plays a significant role in MSME resilience through social networks between traders, customer trust, and community support. Strategies for utilizing social capital include collaboration, joint promotions, sharing supplier information, and forming small groups to monitor market trends. Obstacles encountered include conflicts of interest between traders, low participation of network members, and differences in priorities that limit the effectiveness of social capital.